2018
DOI: 10.1186/s13104-018-3226-8
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic management of mandibular canine with two roots and two canals: a rare case report

Abstract: BackgroundIn general, mandibular canines have a single root and a single canal. The occurrence of two roots and two canals is a rare entity ranging from 1 to 5%. The anatomy of root canal morphology plays a decisive role in determining the conditions under which endodontic treatment can be performed effectively. Successful endodontic treatment comprises proper diagnosis, meticulous cleaning and shaping followed by three dimensional obturation. Failure to do so may lead to postoperative diseases, pain and furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…5 According to the literature, CVM stages strongly correlate with skeletal maturity but some studies show a weak correlation. 11,18 The relation between left mandibular canine and skeletal maturation in the Pakistani population was 0.787 in this study. As a result, it may be concluded that the mandibular canine is an important factor in determining skeletal maturity.…”
Section: Discussionsupporting
confidence: 46%
“…5 According to the literature, CVM stages strongly correlate with skeletal maturity but some studies show a weak correlation. 11,18 The relation between left mandibular canine and skeletal maturation in the Pakistani population was 0.787 in this study. As a result, it may be concluded that the mandibular canine is an important factor in determining skeletal maturity.…”
Section: Discussionsupporting
confidence: 46%
“…Most other original research studies that investigated the canine has been conducted outside the Saudi population [20][21][22][23][24][25][26][52][53][54][55][56][57][58][59][60] as presented in Table 2. Other papers, such as case report studies, 51,[61][62][63][64][65][66][67] studied the RMCC among Western populations. Therefore, this review aimed to search studies in the form of original research and/or case reports on canine RMCC on the basis of Vertucci's classification 19,34 among Saudis.…”
mentioning
confidence: 99%
“…Morphologically, mandibular canines usually have only one root and one root canal in approximately 85% of the cases [7]. However, atypical findings like mandibular canine having one root with two root canals and two roots with two root canals have been reported [6][7][8][9]11]. In fact, a rare case of mandibular canine with two roots and three root canals has been reported by Heling et al [12].…”
Section: Discussionmentioning
confidence: 99%
“…The mandibular canine has Vertucci's type I configuration in approximately 85% of the cases [3][4][5]. However, cases may present with two canals in a single root or even less commonly, with two roots and two root canals and inadequate knowledge of such anatomical variations is one of the most common causes of endodontic treatment failure [6][7][8][9][10]. A patient presenting with such root canal anatomy is unpredictable, and the clinician should always be recognizant of such variations that may affect the prognosis.…”
Section: Introductionmentioning
confidence: 99%